Interprofessional Education: Reaching Health Professionals With an Interactive Professional Virtual/Online Event on Advocacy and Policy - Liller, Karen D.; Pruitt, Zachary; Burke, Somer Goad (Frontiers in Public Health, 2020)
Competencies in health policy and advocacy should be developed by all health professionals to effectively advance their professions but also effectively collaborate in interprofessional teams to improve public health. However, the COVID-19 epidemic presents a challenge to reaching students of health professions through face-to-face offerings. To meet this need, the University of South Florida College of Public Health developed asynchronous and synchronous online health policy and advocacy modules delivered to an interprofessional group of students pursuing health careers. After learning policy and advocacy material individually through a self-paced online curriculum, faculty gathered the students for a synchronous online event where they formed collaborative groups. In interprofessional teams, students prepared and presented advocacy briefs that were critiqued by the faculty. Post-event evaluation results showed that most students strongly agreed that the interprofessional event was very effective, and they all would recommend the program to other students. Universities and colleges educating students of health professions can take advantage of the technologies employed to keep students safe in the COVID-19 pandemic and still reach students effectively with interprofessional health policy and advocacy content.